Protein losing enteropathy: A rare complication of ulcerative colitis - Sultan Turel; Ali Kirik; Berkay Kuscu; Ugur Ergun; Mehmet Nur Kaya; Teoman Dogru (Medicine Science, 2019)
Protein-losing enteropathy (PLE) is a rare gastrointestinal condition that has been related to inflammatory bowel disease (IBD), namely ulcerative colitis (UC) and Crohns disease (CD). These pathologies damage the mucosal integrity, thereby leading to an increased transfer of plasma proteins into the bowel lumen. Because of its rarity, incidence and prevalence of this condition are not well known. Depending upon the underlying cause, the clinical course of PLE is highly variable, but mainly consists of edema, ascites, pericardial and pleural effusions. Here, we report a case of PLE caused by UC, in which total colectomy lead to complete improvement of hypoalbuminemia. [Med-Science 2019; 8(4.000): 1041-3]